2007
DOI: 10.1210/jc.2006-1683
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Adiponectin and Leptin during Refeeding of Female Anorexia Nervosa Patients

Abstract: Our study demonstrates hyperadiponectinemia, increased adiponectin HMW isoform, and increased insulin sensitivity in adolescent AN female patients and reversal of these findings with weight rehabilitation. We hypothesize that increased adiponectin levels may have a protective role in maintaining energy homeostasis during extreme malnourishment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
49
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 26 publications
12
49
2
2
Order By: Relevance
“…Generally, assessment of total adiponectin showed a bi-phasic pattern with a temporary increase in the levels of this adipokine observed at the beginning of treatment and a gradual decrease thereafter [18,27,33]. However, in the current PRACE ORYGINALNE study we did not find significant differences between adiponectin levels when comparing AN individuals before and after refeeding.…”
Section: Prace Oryginalnecontrasting
confidence: 77%
See 2 more Smart Citations
“…Generally, assessment of total adiponectin showed a bi-phasic pattern with a temporary increase in the levels of this adipokine observed at the beginning of treatment and a gradual decrease thereafter [18,27,33]. However, in the current PRACE ORYGINALNE study we did not find significant differences between adiponectin levels when comparing AN individuals before and after refeeding.…”
Section: Prace Oryginalnecontrasting
confidence: 77%
“…In addition, there were no differences between the two groups of AN. The group of Modan-Moses was the first to report an increased proportion of HMW isoform in the malnourished phase of AN, followed by a decrease after weight gain to levels similar to control participants [33].Terra et al also observed a marked increase in HMW adiponectin in AN [18]. These authors found as well that HMW adiponectin related negatively with disease duration after adjustment for age.…”
Section: Prace Oryginalnementioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, serum adiponectin inversely correlates with obesity, 2 while higher adiponectin levels have been documented in conditions of extreme malnourishment and severe energy deprivation. 17,18 Considering the aforementioned data, the results of our study could suggest that acute physical exercise per se does not regulate serum adiponectin levels, regardless of the intensity and the duration. Furthermore, the action of adiponectin as a starvation signal and a regulator of energy homeostasis is likely exerted in conditions of chronic energy restriction rather than acutely established energy deficit.…”
Section: The Effect Of Strenuous Prolonged Aerobic Exercise and Acutementioning
confidence: 68%
“…This lack of correlation with inflammatory mediators suggests that the levels of adiponectin multimers might be more linked to changes in glucose and lipid metabolisms at young ages. Figure 1 resumes the reported associations between total, HMW and LMW adiponectin with inflammatory mediators, hormones and other factors [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Adiponectin and Its Isoformsmentioning
confidence: 99%